Architectural techniques - St-Laurent, Francois; Evrard, Anne; Hanessian, Lu; Coscient Inc.; CSM Productions; Films for the Humanities (Firm) (Princeton, NJ : Films for the Humanities & Sciences, 1995)
Shows how architecture has changed through time with the advent of new technologies and materials, and how the newest technologies are being used to preserve endangered monuments
Producer, François St-Laurent, Anne Evrard ; editors, Jo Lussier, Richard Jutras
Host and narrator : Lu Hanessian
Keywords: Architecture and technologies; Architecture -- Technologies innovations; Structural engineering; Architecture -- Designs and plans